Effect of Work Experience, Independence, Objectivity and Integrity on the Quality of Auditor's Audit Results with Motivation as a Moderating Variable - Arifin Ade Neser; July Kristiani Br Sitepu; Wilsa Road Betterment Sitepu (Green Publisher Indonesia, 2022)
The purpose of this study was to analyze the effect of work experience, independence, objectivity, integrity, on the quality of audit results with motivation as a moderating variable. This type of research is quantitative. The population in this study were auditors at the Financial and Development Supervisory Agency (BPKP) of North Sumatra, Medan with a sample of 70 auditors, which were taken using purposive sampling method. The research instrument used a questionnaire and the analytical technique used was multiple linear regression analysis. The results of the study indicate that integrity and objectivity have an effect on audit quality. Work Experience, Independence, motivation as moderating variables have no effect on Audit Quality.